2007
DOI: 10.1074/jbc.m704841200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Zn2+-sensitive Soluble Exopolyphosphatase from Trypanosoma cruzi Depletes Polyphosphate and Affects Osmoregulation

Abstract: We report the cloning, expression, purification, and characterization of the Trypanosoma cruzi exopolyphosphatase (TcPPX). The product of this gene (TcPPX), has 383 amino acids and a molecular mass of 43.1 kDa. TcPPX differs from most exopolyphosphatases in its preference for short-chain polyphosphate (poly P). Heterologous expression of TcPPX in Escherichia coli produced a functional enzyme that had a neutral optimum pH and was dramatically inhibited by low concentrations of Zn 2؉ , high concentrations of bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…This is relevant because polyP synthesis is not the only determinant of cytosolic P i homeostasis, where the SPX domains and inositol pyrophosphates play a role. In amino acid and metal homeostasis, polyP also constitutes an important polymeric counter-ion to basic amino acids and divalent metal ions (45,46). Basic amino acids can be stored in vacuoles and acidocalcisomes in concentrations of several hundred millimolars.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because polyP synthesis is not the only determinant of cytosolic P i homeostasis, where the SPX domains and inositol pyrophosphates play a role. In amino acid and metal homeostasis, polyP also constitutes an important polymeric counter-ion to basic amino acids and divalent metal ions (45,46). Basic amino acids can be stored in vacuoles and acidocalcisomes in concentrations of several hundred millimolars.…”
Section: Discussionmentioning
confidence: 99%
“…The T. cruzi PPX is similar to the LmPPX although its localization has not been reported. Interestingly, overexpression of TcPPX led to a significant decrease in short-chain poly P and in the staining of acidocalcisomes with DAPI, suggesting that it is also localized to acidocalcisomes (Fang et al 2007b).…”
Section: Acidocalcisome Enzymes Involved In Polyphosphate Synthesis Amentioning
confidence: 99%
“…Acidocalcisomes are enriched in basic amino acids that probably complex with the negatively charged poly P (Rohloff et al 2003). Only a few soluble enzymes have been detected in the acidocalcisomal matrix, including an exopolyphosphatase (PPX) in Leishmania major and Trypanosoma cruzi (Fang et al 2007b), a soluble inorganic pyrophosphatase in Trypanosoma brucei (Lemercier et al 2004), and a metacaspase in Leishmania donovani (Lee et al 2007). Acid phosphatase activity has also been detected using cytochemical methods (Gomes et al 2006).…”
Section: Structural Characteristics and Composition Of Acidocalcisomesmentioning
confidence: 99%
“…It is possible to compare these outcomes with representative historical data sets including the Medical Research Council (MRC) study where the overall survival (OS) in the nontransplanted group for melphalan-prednisone vs cyclophosphamide-thalidomidedexamethasone was 30.6 vs 33.2 months, respectively, and for patients in the transplanted group .64 years of age was 53 months. 2 In the Intergroup Français du Myélome (IFM) 99-06 study comparing melphalan-prednisone with melphalanthalidomide-prednisone and with autologous stem cell transplant (ASCT) with 100 mg/m 2 of melphalan, the OS in each group was 33.2, 51.6, and 38.3 months, respectively. 3 Thus, the 5-year OS of 63% in the current study is good, using this novel sequential approach…”
Section: Institute Of Cancer Research and Royal Marsden Hospitalmentioning
confidence: 99%
“…which is secreted upon platelet activation. 2 In 2006, we showed that polyphosphate of the size secreted by activated platelets is a potent prohemostatic agent, capable of accelerating plasma clotting and substantially delaying fibrinolysis. 3 In the ensuing years, our laboratory and others have further delineated the contributions of polyphosphate to hemostasis and thrombosis, showing in particular that long-chain polyphosphate (of the size that accumulates in microorganisms) is an extremely potent trigger of the contact pathway of clotting, while platelet-sized polyphosphate greatly accelerates downstream clotting reactions, enhances fibrin clot structure, and promotes the feedback activation of factor XI by thrombin.…”
Section: University Of Illinois At Urbana-champaignmentioning
confidence: 99%